An integrative identification guide to the Hydrozoa (Cnidaria) of Bocas del Toro, Panama. Issue 1 (30th November 2018) - Miglietta, Maria Pia; Piraino, Stefano; Pruski, Sarah; Alpizar Gonzalez, Magdalena; Castellanos-Iglesias, Susel; Jerónimo-Aguilar, Sarai; W. Lawley, Jonathan; Maggioni, Davide; Martell, Luis; Matsumoto, Yui; Moncada, Andrea; Nagale, Pooja; et al.
ABSTRACT: This work is the first attempt to assess the biodiversity of the Hydrozoa in the Archipiélago de Bocas del Toro (Panamá, Caribbean Sea) using morphology and molecular taxonomy, and to produce field identification tools to help future identification and monitoring efforts in the area. We sampled, identified, vouchered, and barcoded 112 specimens of Hydrozoa from shallow coastal waters (0–22 m depth) in the Archipiélago de Bocas del Toro. The specimens belong to 70 taxa, of which 53 were identified at the species level, and 17 were identified at the genus or family level. We produced 64 sequences of the large ribosomal subunit of the mitochondrial RNA (mt lsu-rRNA, 16S), the genetic marker generally used for barcoding Hydrozoa. We updated the local checklist that now comprises 118 species, and produced 87 detailed taxon identification tables that display species descriptions augmented with pictures, geographic distribution (worldwide and in Bocas del Toro), GenBank accession numbers for the 16S mitochondrial gene, and a synopsis of the families they belong to.